A Subpopulation of Tegument Protein vhs Localizes to Detergent- Insoluble Lipid Rafts in Herpes Simplex Virus-Infected Cells - Lee, Grace E. (American Society for Microbiology, 2003)
Virion host shutoff (vhs) is a 58-kDa protein encoded by the UL41 gene of herpes simplex virus (HSV). vhs resides within the tegument of HSV, enters the cell cytoplasm at infection, and destabilizes host cell and viral mRNA. Late in infection, vhs must be assembled into the tegument of progeny virions, a poorly understood process. Using an anti-vhs antiserum and Western blotting of total cell or cytoplasmic extracts, we found that vhs is largely insoluble in HSV-infected cells, even in the presence of high levels of salt and the detergent Triton X-100. Furthermore, a subpopulation of vhs appears to be associated with detergent-insoluble lipid rafts and this raft population is enriched in a cytoplasmic fraction which contains assembling and mature HSV particles. Our data raise the possibility that HSV tegument polypeptides associate with membrane rafts, in common with the matrix proteins of a number of other viruses.